In pursuit of foresight : disaster incubation theory re-imagined - Lauder, Mike (Gower, 2015)
Mike LauderMany inquiry reports blame managers for the failures of foresight. These reports are founded on the premise that, with a little more thought, these oversights, which enabled the crisis to occur, would have been avoided. Is it really that simple? These inquiry reports then go on to offer recommendations that may have prevented the events that occurred but may also be the genesis of the next crisis. In many cases these recommendations have failed to avoid the reverse fallacy, that is when an action or omission is seen as being significant in the context of one particular tragedy that leads to a recommendation and is not universally appropriate, as it may have unintended consequences at some point in the future. These recommendations are just another type of failure of foresight. The really important question, however, is whether, without hindsight, it is possible to avoid such failures. An important enabler when trying to avoid such failures of foresight is to be able to identify in advance the factors that might lead to such failure. The issue of failure of foresight is universal and world-wide. Crises occur everywhere and people still struggle to avoid them. Here Mike Lauder provides executives with thinking tools to help them avoid missing the warning signs of the next crisis.--